Robinson Crusoe - Defoe, Daniel (Oxford University Press, 1993)
Robinson Crusoe's account of his life as the sole survivor of a shipwreck on an island somewhere in the Caribbean. Loosely based on a true account of Scottish sailor, Alexander Selkirk.